Money also is sunny in a retiree's world - Svenja Lorenz; Thomas Zwick (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
This paper shows that labor income plays an important positive role for the decision to work after retirement. Especially individuals who have the chance to substantially supplement their pension entitlements have a higher earnings elasticity. Men are more attracted by earnings incentives than women. Also individuals who work until retirement can easier be attracted by financial incentives to work after retirement than those with bridge options. Our analysis is based on a representative and large administrative individual career data set that includes employer information. We use an endogeneity correction model to estimate labor and non-labor financial determinants of labor market participation after retirement.
Keywords: J14; J22; J26; 330; work after retirement; labor and non-labor financial incentives; empirical study